Parthenocarpy induction and reduction of seeds in fruits of ‘Nadorcott’ mandarin - Pereira Gonzatto, Mateus; Griebeler, Sabrina Raquel; Klamer de Almeida, Gustavo; de Oliveira Munhoz, Bruno; Sulzbach, Manuela; Schwarz, Sergio Francisco (Revista Ceres, 2022)
Mandarins commercialization at international market requires seedless fruit production in addition to its ideal organoleptic and visual quality. The objective of the work was to evaluate the efficiency of applications of gibberellic acid and of copper sulfate during anthesis in reducing the number of seeds and in the productive performance of the ‘Nadorcott’ mandarin in the conditions of the southern Brazil. The experiment was performed in an orchard of ‘Nadorcott’ mandarin trees grafted on Poncirus trifoliata. Two applications were conducted at anthesis with different levels and combinations of gibberellic acid and copper sulfate. Also, a net was used as one of the treatments to prevent pollination. The net treatment provided a high frequency of seedless fruits, with greater skin color, however with less production. Gibberellic acid applications increased linearly the frequency of seedless fruits and with a maximum of two seeds. Copper sulphate applications did not affect any evaluated characteristics. Sprays of gibberellic acid of 100 mg L-1 concentration reduce the number of seeds per fruit and increase parthenocarpy, without effect on fruit size and peel color.